2015
DOI: 10.1039/c5cp00034c
|View full text |Cite
|
Sign up to set email alerts
|

Photocarrier recombination dynamics in ternary chalcogenide CuInS2 quantum dots

Abstract: Photocarrier recombination dynamics in ternary chalcogenide CuInS2 quantum dots (CIS QDs) was studied by means of femtosecond transient-absorption (TA) and nanosecond time-resolved photoluminescence (PL) spectroscopy. Under strong excitation, the TA dynamics in CIS QDs is well described by a simple rate equation including single-carrier trapping, free-to-bound recombination, and trap-assisted Auger recombination. Under weak excitation, on the other hand, the PL decays of the QDs are composed of a short-lived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 45 publications
(100 reference statements)
10
79
0
Order By: Relevance
“…Compared to the typical lifetime of tens of ns for CdSe QDs, the PL lifetime of CIS QDs is much longer with an amplitude‐weighted averaged lifetime around 200 ns. Such a long lifetime and multi‐exponential decay behavior have been reported in previous research . The excited‐state dynamics for this type of QDs is still under debate and not clearly understood yet, mainly due to uncertainties in the ternary CIS QD composition, size and shape, and external/internal defects.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Compared to the typical lifetime of tens of ns for CdSe QDs, the PL lifetime of CIS QDs is much longer with an amplitude‐weighted averaged lifetime around 200 ns. Such a long lifetime and multi‐exponential decay behavior have been reported in previous research . The excited‐state dynamics for this type of QDs is still under debate and not clearly understood yet, mainly due to uncertainties in the ternary CIS QD composition, size and shape, and external/internal defects.…”
Section: Resultssupporting
confidence: 60%
“…The excited‐state dynamics for this type of QDs is still under debate and not clearly understood yet, mainly due to uncertainties in the ternary CIS QD composition, size and shape, and external/internal defects. Some initial studies have attributed the short lifetime components to surface or interface defect states and the longer components to intrinsic defect states possibly involving donor–acceptor recombination transitions . Recent studies have suggested that the short lifetime components are related to the band edge surface trapping and/or defect‐induced charge recombination, while the longer one was attributed to subbandgap transition between band edge electrons and Cu vacancy localized holes …”
Section: Resultsmentioning
confidence: 99%
“…The most feasible possibility is three-particle Auger recombination when one carrier is trapped 9 , 12 , 29 . This would require a presence of traps within a silicon band gap.…”
Section: Resultsmentioning
confidence: 99%
“…Auger processes have been largely overlooked in nanocrystal photophysics, and only relatively recently has their significance gained recognition. [16][17][18] The inset to Figure 4E shows the same curves normalized to their plateau magnitudes. Again, the curvature shows very little power dependence, consistent with experiment.…”
Section: Journal Of Physical Chemistry Lettersmentioning
confidence: 94%